Unemployment, poverty and inequality in SA as seen through a feminist political-economy lens - Sibeko, Sbusisiwe (New Agenda: SA Journal of Social and Economic Policy, 2024)
Author information: Sbusisiwe Sibeko is an economist and researcher. She holds a Bachelor of Science in Economics from Duke University and a Masters in the Political Economy of Development from SOAS, University of London. She has worked at the Institute for Economic Justice (IEJ), where her research focus was macroeconomic policy and was the co-Chair of the Budget Justice Coalition (BJC). She considers herself a feminist political economist in training and is determined to be a part of unwinding structural injustice.Background: Much social reproduction is based in households, with women at the forefront, yet this work is still delegated to the periphery of political-economic policy discussions. In this article Sbusisiwe Sibeko provides a feminist political-economic perspective to investigate how women’s bodies and labour might be conceptualised as the ‘last colony’ of accumulation.